Pattern and Outcome of Pulmonary and Extra-pulmonary Tuberculosis in Children: Two Years Study of a Tertiary Care Hospital (Bangladesh Journal of Medicine, 2024)
Background: Bangladesh faces a significant tuberculosis burden, ranking among the highest globally. The country has a high incidence of both tuberculosis and drug-resistant tuberculosis, especially in densely populated urban areas and among marginalized populations. The objective of this study was to evaluate the pattern and outcome of pulmonary and extra-pulmonary tuberculosis in children. Methods: This was a descriptive type of study that was conducted in the Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh, from August 2021 to August 2023. A total of 280 diagnosed children of tuberculosis were enrolled purposively. Data were analyzed by using MS Office tools. Results: Among the participants, 51.1% (143) had pulmonary tuberculosis (PTB), while 48.9% (137) had extra-pulmonary tuberculosis (EPTB). Most patients were young girls aged 5-10 years. All presented with fever, followed by cough with sputum (51%), anorexia, and weight loss (51%). A history of TB contact was common. Of the participants, 185 (66%) completed treatment and were cured; 10 (3.6%) completed treatment but weren’t cured; 14 (5%) were still undergoing treatment; 25 (8.9%) stopped treatment; 7 (2.5%) defaulted; 6 (2.1%) were lost to follow-up; and 3.8% died. The treatment success rate was 94.9%. Conclusion: Pulmonary tuberculosis (TB) is prevalent in pediatric patients, commonly presenting with fever and cough. Despite some discontinuing treatment, most are cured with appropriate antiTB drugs. The DOTS strategy is effective, showing no adverse effects from the drugs.Bangladesh J Medicine 2025; 36: 19-24